Differential protein modulation by ketoprofen and ibuprofen underlines different cellular response by gastric epithelium. Issue 3 (25th August 2017) - Brandolini, Laura; d'Angelo, Michele; Antonosante, Andrea; Villa, Sara; Cristiano, Loredana; Castelli, Vanessa; Benedetti, Elisabetta; Catanesi, Mariano; Aramini, Andrea; Luini, Alberto; Parashuraman, Seetharaman; Mayo, Emilia; et al.
Abstract : Ketoprofen L‐lysine salt (KLS), is widely used due to its analgesic efficacy and tolerability, and L‐lysine was reported to increase the solubility and the gastric tolerance of ketoprofen. In a recent report, L‐lysine salification has been shown to exert a gastroprotective effect due to its specific ability to counteract the NSAIDs‐induced oxidative stress and up‐regulate gastroprotective proteins. In order to derive further insights into the safety and efficacy profile of KLS, in this study we additionally compared the effect of lysine and arginine, another amino acid counterion commonly used for NSAIDs salification, in control and in ethanol challenged human gastric mucosa model. KLS is widely used for the control of post‐surgical pain and for the management of pain and fever in inflammatory conditions in children and adults. It is generally well tolerated in pediatric patients, and data from three studies in >900 children indicate that oral administration is well tolerated when administered for up to 3 weeks after surgery. Since only few studies have so far investigated the effect of ketoprofen on gastric mucosa maintenance and adaptive mechanisms, in the second part of the study we applied the cMap approach to compare ketoprofen‐induced and ibuprofen‐induced gene expression profiles in order to explore compound‐specific targeted biological pathways. Among the several genes exclusively modulated by ketoprofen, our attention was particularly focused on genes involved in the maintenance of gastric mucosa barrier integrity (cell junctions, morphology, and viability). The hypothesis was further validated by Real‐time PCR. Abstract : Ketoprofen and ibuprofen differentially modulate proteins involved in gastroprotection.